1984
DOI: 10.1002/polc.5070710106
|View full text |Cite
|
Sign up to set email alerts
|

The thermal properties of polypropylene

Abstract: The thermodynamic properties of isotactic polypropylene in the fully crystalline, glassy, and molten state are established from 0 to 500 K based on data bank heat capacities and the vibrational frequency spectrum. The seven skeletal vibrations are described by θ3 and θ1 of 91 and 714 K for crystalline polypropylene. For the calculation of Cp − Cv, a Lindemann A0 value of 1.5 × 10−3 K mol/J was found. Calculated and experimental heat capacity data show agreement within an average error of −0.3 ± 1.6%. Glassy po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(101 citation statements)
references
References 26 publications
1
97
1
2
Order By: Relevance
“…The case when x = 0.75 reproduces the experimental DSC well. This value is significantly smaller than the previously reported values (= 0.97 [8] and 0.93 [9]). It is essential to consider the balance among the fractions of alpha-crystal, mesomorphic phase and amorphous phase to obtain the reliable value, otherwise we end up overestimation of the value.…”
Section: Energy Level Of Mesomorphic Phasecontrasting
confidence: 82%
See 1 more Smart Citation
“…The case when x = 0.75 reproduces the experimental DSC well. This value is significantly smaller than the previously reported values (= 0.97 [8] and 0.93 [9]). It is essential to consider the balance among the fractions of alpha-crystal, mesomorphic phase and amorphous phase to obtain the reliable value, otherwise we end up overestimation of the value.…”
Section: Energy Level Of Mesomorphic Phasecontrasting
confidence: 82%
“…Although rough estimation of the energy level of mesomorphic phase is possible by assuming the original fraction of mesomorphic phase transforms into the same fraction of alpha-crystal [8,9], in reality the balance among the fractions of alpha-crystal, mesomorphic phase and amorphous phase as a function of temperature should be taken into consideration for the more precise estimation.…”
Section: Introductionmentioning
confidence: 99%
“…The mesomorphic modification of ZieglerNatta iPP is described in literature as a structure with an intermediate order between the crystal and the amorphous phases, being constituted by a paracrystalline, microcrystalline, nanocrystalline or a conformationally disordered structure. [38][39][40][41][42][43] Therefore, variation of the different mechanical parameters and of the shape of the stress-strain curves in these two copolymers with the highest 1-octadecene contents (CiPOD5.3 and CiPOD7.6) should be also related, additionally to the decrease in number of ordered entities and their size. Thus, the size, perfection, amount and morphological details of ordered crystallites are key parameters in determining the mechanical response in these CiPPOD copolymers and they become softer as comonomer content increases, irrespective of the lattice being monoclinic or mesomorphic.…”
Section: Resultsmentioning
confidence: 99%
“…This intermediate state is between ordered and amorphous phases, and widely known by various names such as "quenched" [19], "mesomorphic" [20,21], "paracrystalline" [22], nano-crystallites [23], condis crystal [24] and a well known "smectic" phase [25][26][27]. Later, it was also found that the smectic phase could be obtained by cold drawing of iPP film at room temperature [28][29][30].…”
Section: Introductionmentioning
confidence: 99%